PROTOTYPE MINI FIRE ENGINE WITH ULTRASONIC AND FLAME SENSOR USING ARDIUNO UNO - Ari Setyo; Dimas Fannyi Hebrasianto Permadi (Universitas Islam Balitar, 2017)
Prototype Mini Fire Engine with Ultrasonic and Flame Sensor Using Arduino Uno hasseveral components, namely: 3 ultrasonic sensors to read objects using the wall avoidermethod, fire sensors to detect hotspots, Arduino uno as the brain, l293D motor as IC, DCmotor for driving fire engine, delay to activate the pump until it can spray to the point of fire,and the battery as a source of robot voltage. All strung together to become a fire fightingrobot. How it works Prototype Mini Fire Engine with Ultrasonic and Flame Sensors UsingArduino Uno is a robot that runs on a predetermined lane that has the shape of the letter U.The robot detects objects to the point of fire until the fire sensor lights up and the robot willstop. If the fire sensor detects a hotspot, the delay will start to activate the pump so that itcan spray water to the fire source.